Les logiques de dé-professionnalisation des universitaires - Sandrine Garcia (Cahiers de la Recherche sur l'Education et les Savoirs)
This paper tackles the impact of increasing pedagogical expertise, which, within the frame of Bologna process, allows to restrain the professional autonomy of academics. Actually this expertise induces a division of labour between the academics and the experts that are in charge of defining the pedagogical quality.Our work shows how the complex process of alliances in between political forces, unions and academics has open the way to deprofessionalisation of these latter (in the sense that now they are not the only ones that are expertising their own practise) . More peculiarly, it should be pointed out that the unions that represents the academics after having been ruled out of all the major political committees that have worked on the definition of Bologna process, and after having being disowned by their traditional allied the student unions (which have support the so called “Loi sur l’autonomie des Universités”) are now forced to relieve the experts talking that leads to what we have called deprofessionalisation of the academics.